Genetic dissection of the biochemical activities of human DNA repair protein, APE1 - Redrejo-Rodriguez, M.; Mursalimov, A.; Koshenov, Z.; Zhakupova, K.; Saparbaev, M. K.; Ishchenko, A. A.; Matkarimov, B. (Nazarbayev University, 2014)
Human apurinic/apyrimidinic endonuclease 1 (APE1) is a key DNA repair enzyme involved in both base excision repair (BER) and nucleotide incision repair (NIR) pathways. In the BER pathway, APE1 cleaves DNA at AP sites and 3'-blocking moieties generated by DNA glycosylases. In the NIR pathway, APE1 incises DNA 5' to a number of oxidatively damaged bases. Here we propose to identify and characterize critical amino acids of APE1 involved in either BER and/or NIR functions by using the alignment of the known three-dimensional (or tertiary) structures of Xth family AP endonucleases including the Methanothermobacter thermautotrophicus Mth212, Bacillus subtilis ExoA (1), E. coli Xth and human APE1 proteins (2).
Keywords: DNA repair; APE1 protein; endonucleases; glycosylases; amino acid; biochemical